RANCANG BANGUN PERMAINAN TRADISIONAL KALIMANTAN TENGAH BAGAPIT MENGGUNAKAN ALGORITMA ALPHA BETA DAN MTD(F) - Ressa Priskila; Putu Bagus Adidyana Anugrah Putra (Universitas Palangka Raya, 2023)
Bagapit is a traditional game from Central Kalimantan. This game is usually done in free time or after doing daily tasks. This traditional game has begun to be forgotten, because of the rapid development of technology. In this day and age, people prefer to play games with gadgets. Therefore, to preserve and introduce this game to the wider community who are already familiar with technology, it is necessary to create a mobile-based bagapit game application. This game was made using the Multimedia Development Life Cycle (MDLC) method. This method consists of 6 stages, namely concept, design, collecting material, assembly, and testing. In this research, the system design is made by making use case diagrams, activity diagrams, storyboards, and User Interface designs. The material collected at the material collecting stage consists of background, object images, and audio. To determine the steps in the game, the Alpha Beta pruning algorithm and the MTD(f) algorithm are used. The making of this bagapit game uses the Godot Engine which uses the GDScript programming language. Testing is carried out using the black box testing method to ensure all functions in the game can function properly. This game consists of 3 levels that players can choose from. It is hoped that this game can introduce, provide insight, and preserve the bagapit game which is a traditional game typical of Central Kalimantan to the general public.